Bahasa Inggris - Rindiani Rindiani; Dewi Komala Sari; Kumara Adji Kusuma (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the effect of brand ambassadors, brand image, and halal labeling on purchasing decisions for Scarlett Whitening products. This study uses a descriptive quantitative approach with a population of Sidoarjo people who have bought Scarlett Whitening products and are more than 17 years old. The sample was selected using purposive sampling technique. Data collection was carried out through distributing questionnaires, where respondents' answers were measured using a Likert scale. Data analysis using the SmartPLS (Partial Least Square) 4.0 tool. The results of this study prove that Brand Ambassador has an effect on purchasing decisions on scarlett whitening products. In addition, Brand Image affects purchasing decisions on scarlett whitening products and Halal Label affects purchasing decisions on scarlett whitening products.